Homogeneous doping of entire perovskite solar cells via alkali cation diffusion from the hole transport layer. Issue 14 (29th March 2021) - Chen, Mengjiong; Qiao, Hong Wei; Zhou, Ziren; Ge, Bing; He, Jingjing; Yang, Shuang; Hou, Yu; Yang, Hua Gui
Abstract : Alkali metal ions spontaneously diffuse from the hole transport layer into perovskite layer and electron transport layer, which could enhance the conductivity of NiO x films and modulate perovskite layer electronic states, simultaneously. Abstract : Organic–inorganic hybrid perovskite materials have attracted enormous attention owing to their extraordinary progress in both power conversion efficiency and stability. However, nonradiative carrier recombination occurring in the perovskite films and interface hinders its commercial viability as the next-generation photovoltaics. Doping with metal cations has been demonstrated to be efficacious for controlling charge transport and reducing charge recombination for perovskite solar cells. Herein, we report the homogeneous doping of entire perovskite solar cells by alkali cations via a dopant diffusion strategy from the hole transport layer. It was found that Rb + ions enhanced the conductivity and optimized the energy level alignment. The diffused Rb + ions within the perovskite layer could further reach the bulk films with modulated electronic states. The power conversion efficiency of the perovskite solar cell based on 1.0% Rb + -doped NiO x boosts to 21.80% with a high fill factor of 0.824. Unencapsulated Rb + -doped NiO x photovoltaic devices maintained 93.3% of their initial efficiency after storage in air for 1200 h.